2020
DOI: 10.3390/clockssleep2030022
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA: A Key Player for the Interplay of Circadian Rhythm Abnormalities, Sleep Disorders and Neurodegenerative Diseases

Abstract: Circadian rhythms are endogenous 24-h oscillators that regulate the sleep/wake cycles and the timing of biological systems to optimize physiology and behavior for the environmental day/night cycles. The systems are basically generated by transcription–translation feedback loops combined with post-transcriptional and post-translational modification. Recently, evidence is emerging that additional non-coding RNA-based mechanisms are also required to maintain proper clock function. MicroRNA is an especially import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 207 publications
(257 reference statements)
0
17
0
Order By: Relevance
“…Evidence shows that the expressions of the mature or precursor forms of some miRNAs exhibit circadian and/or diurnal rhythms and are suggested to be involved in circadian rhythm regulation and physiological function [ 69 , 70 ]. The miRNAs miR-155, miR-27b-3p, miR-211, and miR-142 have been described to regulate the rhythmic expression of Bmal1 mRNA and protein levels [ 69 , 71 , 72 ]. HIV infection has been associated with irregularities in physiological functions related to circadian rhythm [ 37 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that the expressions of the mature or precursor forms of some miRNAs exhibit circadian and/or diurnal rhythms and are suggested to be involved in circadian rhythm regulation and physiological function [ 69 , 70 ]. The miRNAs miR-155, miR-27b-3p, miR-211, and miR-142 have been described to regulate the rhythmic expression of Bmal1 mRNA and protein levels [ 69 , 71 , 72 ]. HIV infection has been associated with irregularities in physiological functions related to circadian rhythm [ 37 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, intraperitoneal injection of curcumin in animals was chosen in the present study.In the future, improving bioavailability of curcuminand selectinga proper administration routewould be important for its application in treating diabetic kidney disease. Second, growing evidence has shown that the sleep circadian rhythm significantly associates withthe expression of mircoRNA including mir-29a [46]. Due to the fact that miR-29a is rhythmically expressed and involves the regulation of core clock components, mice that were intraperitoneally injected with curcumin or were sacrificed at different Zeitgeber times (ZT) or circadian times (CT) may probably lead to differential outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the levels of microRNA-125a, microRNA-126, and microRNA-146a are significantly lower in short-sleep compared with normal sleep groups. Dysregulated miRNA-146A in patients with fatal familial insomnia causes increased tau hyperphosphorylation [ 6 ].…”
Section: Effect Of Micrornas On Primary Sleep Disorders Associated With Epilepsymentioning
confidence: 99%
“…MicroRNAs whose regulation affects sleep homeostasis and circadian rhythm include microRNA-107, microRNA-124, micorRNA-125a-3p, microRNA-132, microRNA-182, microRNA-126, and microRNA-146a [ 6 , 7 ]. MicroRNA-124 regulates the development of neurons by controlling key differentiation factors such as REST (repressor element-1 silencing transcription factor) and PTBP1 (polypyrimidine tract-binding protein 1) as well as maturation through effects on CREB (CRE binding protein―cAMP response element).…”
Section: Introductionmentioning
confidence: 99%